Sulfur - fluorine bond in PET radiochemistry - Giancarlo Pascali; Lidia Matesic; Bo Zhang; Andrew T. King; Andrea J. Robinson; Alison T. Ung; Benjamin H. Fraser (SpringerOpen, 2017)
Abstract The importance of the sulfur-fluorine bond is starting to increase in modern medicinal chemistry literature. This is due to a better understanding of the stability and reactivity of this moiety depending on the various oxidation states of sulfur. Furthermore, several commercial reagents used for mild and selective fluorination of organic molecules are based on the known reactivity of S-F groups. In this review, we will show how these examples are translating into the 18F field, both for use as stable tags in finished radiopharmaceuticals and as mildly reactive fluoride-relay intermediates. Finally, we also discuss current opportunities where examples of non-radioactive S-F applications/chemistry may be translated into future 18F radiochemistry applications.